2022
DOI: 10.3390/ijms23179843
|View full text |Cite
|
Sign up to set email alerts
|

Blood RNA Sequencing Indicates Upregulated BATF2 and LY6E and Downregulated ISG15 and MT2A Expression in Children with Autism Spectrum Disorder

Abstract: Mutations in over 100 genes are implicated in autism spectrum disorder (ASD). DNA SNPs, CNVs, and epigenomic modifications also contribute to ASD. Transcriptomics analysis of blood samples may offer clues for pathways dysregulated in ASD. To expand and validate published findings of RNA-sequencing (RNA-seq) studies, we performed RNA-seq of whole blood samples from an Israeli discovery cohort of eight children with ASD compared with nine age- and sex-matched neurotypical children. This revealed 10 genes with di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 67 publications
0
3
0
Order By: Relevance
“…RIN values were determined for all RNA samples from the three LCL cohorts ( N = 39; Table 1) by an automated electrophoresis process using the TapeStation system (Agilent). Additionally, we applied nucleic acid quantitation by using the Qubit™ RNA BR Assay Kit (Invitrogen™, Thermo Fisher Scientific) as described for a recent RNA‐seq project from our lab (Voinsky et al, 2022).…”
Section: Methodsmentioning
confidence: 99%
“…RIN values were determined for all RNA samples from the three LCL cohorts ( N = 39; Table 1) by an automated electrophoresis process using the TapeStation system (Agilent). Additionally, we applied nucleic acid quantitation by using the Qubit™ RNA BR Assay Kit (Invitrogen™, Thermo Fisher Scientific) as described for a recent RNA‐seq project from our lab (Voinsky et al, 2022).…”
Section: Methodsmentioning
confidence: 99%
“…Feldner-Busztin et al 42 indicated the potential of the technologies while emphasizing the need to increase the sample size for each omics and the overall overlapping omics data per sample, namely the genomics, epigenomics, transcriptomics and metabolomics per sample. A range of analytical techniques are applied in several papers covering genomics 32 , RNA signature 30,43 , proteomics 29 , and metabolomics 25,28 . In particular, two high-level bioinformatics annotation engines (Gene Ontology: geneontology.org; and KEGG: www.genome.jp/kegg/) are applied across these patient-derived bioinformatics datasets to permit classification of genes, RNA, proteins and metabolites.…”
Section: Bioinformatics Integrationmentioning
confidence: 99%
“…Notably, in our recent RNA‐sequencing study of whole blood samples from 73 Israeli and American children with ASD compared with 26 matched neurotypically developing children, we observed reduced expression of MT2A , a gene coding for metallothionein 2A (FD = 0.72; p = 0.0057). [ 26 ] Metallothioneins play a key role in the detoxification of heavy metals and act as antioxidants, protecting cells against hydroxyl free radicals, including from neuronal damage by excessive NO. [ 27 , 28 , 29 ] It could therefore be that the reduced blood MT2A mRNA in children with ASD is implicated in the elevated tyrosine nitration of proteins, following peroxynitrite interaction with proteins, as observed by the Amal team.…”
mentioning
confidence: 99%